RNA at 92°C: The non-coding transcriptome of the hyperthermophilic archaeon Pyrococcus abyssi - Toffano-Nioche, Claire (Landes Bioscience, 2013)
The non-coding transcriptome of the hyperthermophilic archaeon Pyrococcus abyssi is investigated using the RNA-seq technology. A dedicated computational pipeline analyzes RNA-seq reads and prior genome annotation to identify small RNAs, untranslated regions of mRNAs, and cis-encoded antisense transcripts. Unlike other archaea, such as Sulfolobus and Halobacteriales, P. abyssi produces few leaderless mRNA transcripts. Antisense transcription is widespread (215 transcripts) and targets protein-coding genes that appear to evolve more rapidly than average genes. We identify at least three novel H/ACA-like guide RNAs among the newly characterized non-coding RNAs. Long 5′ UTRs in mRNAs of ribosomal proteins and amino-acid biosynthesis genes strongly suggest the presence of cis-regulatory leaders in these mRNAs. We selected a high-interest subset of non-coding RNAs based on their strong promoters, high GC-content, phylogenetic conservation, or abundance. Some of the novel small RNAs and long 5′ UTRs display high GC contents, suggesting unknown structural RNA functions. However, we were surprised to observe that most of the high-interest RNAs are AU-rich, which suggests an absence of stable secondary structure in the high-temperature environment of P. abyssi. Yet, these transcripts display other hallmarks of functionality, such as high expression or high conservation, which leads us to consider possible RNA functions that do not require extensive secondary structure.